Sex education for teenager with visual art therapy podcast - Albert Agung Juan Datu; Adrian Nugrahadi; Mikhael Kristianto G; Yesaya Imanuel Nelwan (Southeast Asian Journal of Technology and Science, 2022)
At this time, sex education is a very serious concern, because most parents in Indonesia still consider sex education a taboo subject. Sex education is an act of providing understanding and knowledge of body organs, reproductive organ functions and genital development. Therefore, this study is a new breakthrough because researchers use podcasts and youtube media in providing information, where the two media are platforms that are very loved by today's teenagers which aim to provide an understanding of the importance of sex education and prove that YouTube can be a medium. interesting learning. This study involved 30 respondents which the researchers focused on were adolescent respondents from the age of 15-21 years. The method used in this research is quantitative with survey type using data collection tools and using google form. Not without reason, this research is expected to be understood by today's youth how sex education is very important and respecting and caring for one's own body is very important by using the Visual Art Therapy method. The results of this study were as many as 21 responses or 70% of adolescents aged 15-30 years who expressed their opinion on the lessons that can be drawn from watching sex education video podcasts.